2016
DOI: 10.1515/agr-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Meteorological Phenomena “Frozen Rain” on the Forestry Vegetation. Case Study: Maierus Forest Dept., Brasov County (Romania)

Abstract: Liquid precipitation that freezes on contact with the surface of the underlying components represent a major risk meteorological phenomena affecting, among other things, the high proportion, forest vegetation. The phenomen occurs with a relatively high frequency, every few years, depending on specific mechanisms aggregation on atmospheric physics, needed to its genesis. Affected areas suffer significant changes in structure and composition of forest vegetation. Such a phenomen it was in the first decade of Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In Romania, freezing rain phenomenon was described by Murarescu et al (2016), on the northern of Persani Mountains, who observed it on 2691.6 hectares of the Măieruş Forest Department, in Brasov County. The main objective is to determine how the forest stands were affected by the freezing rain and identifying the optimal solutions for ecological reconstruction and prevention against significant damages, in the case of repeated occurrence of the phenomenon.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Romania, freezing rain phenomenon was described by Murarescu et al (2016), on the northern of Persani Mountains, who observed it on 2691.6 hectares of the Măieruş Forest Department, in Brasov County. The main objective is to determine how the forest stands were affected by the freezing rain and identifying the optimal solutions for ecological reconstruction and prevention against significant damages, in the case of repeated occurrence of the phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the population of trees decreases, which negatively influences the functional role of the forest. Furthermore, the quality of the remaining trees is also reduced, as growths are smaller, tree crowns are sparser, and health, fruiting capacity and natural regeneration are diminished, these aspects would not have occurred naturally (Murarescu et al, 2016, Constandache at al., 2018. The impact of the execution or, on the contrary, of the non-execution of the appropriate silvicultural works, in the studied forest stands, led to different effects, depending on other important characteristics, such as: composition, crown consistency, slenderness coefficient, diameter, height, age, slope (Murarescu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation